Hell, Heaven, Neither, or Both: the Afterlife and Sider's Puzzle - Joaquin, Jeremiah Joven (Sophia, 2019)
Theodore Sider's puzzle in Hell and Vagueness has generated some interesting responses in the past few years. In this paper, I explore yet another possible solution out of the conundrum. This solution implies three ways of denying a binary conception of the afterlife. I argue that while these solutions might first seem tenable, they might still succumb to a Sideresque revenge puzzle.